Site Evaluation - Hickman, John S.; Finnel, Paul R.; Townsend, Margaret A. (My University, 1998)
Evaluating soils and geologic characteristics of a farmstead to protect groundwater.
EP40_1998-08
Keywords: EP40; Environment and Natural Resources; Lawn and Garden; EP